2008
DOI: 10.1111/j.1464-5491.2008.02544.x
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a new incentive and target‐based contract for family physicians in the UK: good for older patients with diabetes but less good for women?

Abstract: The introduction of the nGMS contract was associated with a rise in the recording of patients with diabetes and the recording of diabetes-related quality indicators. However, women have not benefited equally from the nGMS contract. Strategies are needed to further improve the ascertainment of quality measures and care for women with diabetes, to lessen the potential burden of morbidity amongst female patients in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 12 publications
2
38
0
Order By: Relevance
“…An IMPACT modelling study to examine the relationship between socioeconomic status and the factors that explain the declining rates of CHD mortality in the UK between 2000 and 2007 found no evidence of inequity in the delivery of a wide range of interventions [13]. Our findings therefore broadly concur with those of these studies and a number of other individual-level studies [ 2022] although they conflict with those of several ecological studies [ 1418 ] and studies of UK populations during the 1990’s [47–49] that reported evidence of inequity in primary care elements of CHD healthcare.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…An IMPACT modelling study to examine the relationship between socioeconomic status and the factors that explain the declining rates of CHD mortality in the UK between 2000 and 2007 found no evidence of inequity in the delivery of a wide range of interventions [13]. Our findings therefore broadly concur with those of these studies and a number of other individual-level studies [ 2022] although they conflict with those of several ecological studies [ 1418 ] and studies of UK populations during the 1990’s [47–49] that reported evidence of inequity in primary care elements of CHD healthcare.…”
Section: Discussionsupporting
confidence: 87%
“…A large individual-level UK study of secondary prevention of CHD found no evidence of inequity, and some findings suggested that more deprived groups were more likely to receive treatment [ 19 ]. UK-based individual-level studies of the management of diabetes found no evidence of inequity in the prescribing of antihypertensive medication and lipid-lowering therapy [ 2022 ]. Other studies have reported clear evidence of inequity in the use of percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) in the UK [ 23–29 ].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] It is also reassuring to note that the reported decrease in the rate of smoking (6%) was similar to that reported in the General Household Survey. 1 The mean rate of smoking in 2002 was also considerably lower than the mean rate of smoking reported in Europe (33%), 22 but more than found in a national survey in the US (21%; 2005).…”
Section: Comparison With Existing Literaturementioning
confidence: 51%
“…In fact, throughout these studies a closing gap has been identified for performance differences. A small difference implicating less P4P achievement for female as compared to male patients was found[46,49,60,61]. One should take into account that no randomized intervention studies have reported equity of care results.…”
Section: Resultsmentioning
confidence: 99%